PENGELOLAAN MADRASAH DALAM PERSPEKTIF MANAJEMEN MUTU TERPADU (Studi Di MI Plus Al Islam Dagangan Madiun) - Katni .; Adib Khusnul Rois (MUADDIB Jurnal Kependidikan dan Keislaman, 2015)
This study aims to discuss about the school (madrasah) management and the result of excellent school management on the integrated quality management perspective. It was a qualitative research with interview, observation, and documentation in collecting the data. The result of this research were: 1. the management of MI Plus Al Islam, Dangangan Madiun was including (a) Human resource: the principle management with firm, open, solid team, and focus on customer services quality, (b) student management: Islamic religion and values teaching in everyday life, local content for the development of students skill and creativity, (c) graduate competence standard: creating their own quality standardbased on SWOT analysis, without disobeying the government regulations. The quality is designed by strengthening the local content, self-development, and life skill education. (d) Funding management and institutional independence, including: fixed and non-fixed donors, canteen management, and varied payment system. 2. The quality management result was a solid team work and cooperation among management aspects and totally wholehearted services quality, selective and strict acceptance system to produce a quality teachers, improvement strategy and new breakthroughs on education quality improvement with fixed and non-fixed donors, as well as an optimal canteen management as a form of entrepreneurship and funding source for the school independence.This study aims to discuss about the school (madrasah)management and the result of excellent school management on theintegrated quality management perspective. It was a qualitative researchwith interview, observation, and documentation in collecting the data. Theresult of this research were: 1. the management of MI Plus Al Islam,Dangangan Madiun was including (a) Human resource: the principlemanagement with firm, open, solid team, and focus on customer servicesquality, (b) student management: Islamic religion and values teaching ineveryday life, local content for the development of students skill andcreativity, (c) graduate competence standard: creating their own qualitystandardbased on SWOT analysis, without disobeying the governmentregulations. The quality is designed by strengthening the local content,self-development, and life skill education. (d) Funding management andinstitutional independence, including: fixed and non-fixed donors, canteenmanagement, and varied payment system. 2. The quality managementresult was a solid team work and cooperation among managementaspects and totally wholehearted services quality, selective and strictacceptance system to produce a quality teachers, improvement strategyand new breakthroughs on education quality improvement with fixed andnon-fixed donors, as well as an optimal canteen management as a form ofentrepreneurship and funding source for the school independence.